Paleogene sediment complex - Geological factors impacting on its reservoir quality and hydrocarbon potential - San, Ngo Thuong; Hoang, Cu Minh; Hoan, Phung Khac (Petrovietnam Journal, 2013)
The Paleogene reservoir complex has diverse facies which change rapidly in lateral and vertical direction. Its depositional environment is determined as alluvial, deltaic and tidally affected lacustrine, and rarely with shoreline facies. The variety in sedimentary facies and lithological heterogeneity are the main causes for the anisotropy in porosity and permeability of the Paleogene reservoirs, reducing field exploration and development efficiency as well as the application of secondary exploitation in order to increase the oil recovery. Reservoir quality is resulted from the combined effects of primary diagenetic elements and secondary alteration. The secondary deformation has bidirectional influence on the reservoir quality, reducing the primary porosity and forming the secondary porosity as well. The dual porosity is one of the important properties of the Paleogene reservoir that should be considered in production management. Secondary fractures could potentially increase the flow in the tight Paleogene reservoirs. The production from Paleogene reservoir is still small, not corresponding to the potential of Paleogene formation as rich source rock. The Late Eocene-Oligocene reservoir, therefore, needs to be investigated and sufficiently evaluated as a potential hydrocarbon bearing play in order to enhance production and reserves.